Stability analysis of relay access protocol (RAP) using fuzzy logic in wireless sensor networks - Azamuddin, Abdul Rahman; M. N. M., Kahar; Wan Isni Sofiah, Wan Din (IOP Publishing, 2020)
Cluster Head (CHs) determination is critical whereas the combination of input parameters is expected to play an important role. However, each WSN's protocol uses a different combination of input parameters based on residual energy and several other input parameters, which produce different amount of energy consumption. Besides, most of the previous works on cluster heads selection do not take received signal strength indication (RSSI) into consideration. As a result, the sensor nodes with bad RSSI can be elected as CHs which lead to an increase in energy consumption. Moreover, the CHs use single-hop communication to forward their sensed data to the Base Station (BS). This results in high energy consumption and consequently, decrease the network lifetime. In this case, the inter-node distances may degrade the performance of the network due to long distance. Thus, this paper proposed a Relay Access Protocol (RAP) in order to reduce energy consumption in cluster-based wireless sensor networks (WSNs). The RAP protocol is a 2-tier protocol used for energy efficiency by selecting Cluster Heads (CHs) based on Fuzzy Logic (FL). The performance of the proposed protocol was evaluated under two different scenarios and compared with existing protocols through simulations. The experimental results show that the proposed scheme outperformed the existing protocols in terms of First Node Dead (FND) and Last Node Dead (LND) in all of the scenarios.